2020
DOI: 10.3390/en13123134
|View full text |Cite
|
Sign up to set email alerts
|

Determination of High Temperature Corrosion Rates of Steam Boiler Evaporators Using Continuous Measurements of Flue Gas Composition and Neural Networks

Abstract: The use of low-emission combustion techniques in pulverized coal-fired (PC) boilers are usually associated with the formation of a reduced-gas atmosphere near evaporator walls. This increases the risk of high temperature (low oxygen) corrosion processes in coal-fired boilers. The identification of the dynamics and the locations of these processes, and minimizing negative consequences are essential for power plant operation. This paper presents the diagnostic system for determining corrosion risks, based on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The second disadvantage is the lower energy value of solid biofuels compared to fossil fuels. It is related to the need to introduce a larger stream of fuel mixture into the process than in the case of only burning fossil fuels [3]. Another example of the degradation of some elements of a heat block are heated surfaces, where corrosion and corrosion-erosion processes are intensified.…”
Section: Introductionmentioning
confidence: 99%
“…The second disadvantage is the lower energy value of solid biofuels compared to fossil fuels. It is related to the need to introduce a larger stream of fuel mixture into the process than in the case of only burning fossil fuels [3]. Another example of the degradation of some elements of a heat block are heated surfaces, where corrosion and corrosion-erosion processes are intensified.…”
Section: Introductionmentioning
confidence: 99%
“…The determined risk of failure is used to define the safety of further operation. In Hardy's et al paper [12], the corrosion-related risk is described. A diagnostic system for the evaporator walls of a coal-fired boiler was developed to predict the risk of a failure by measuring the exhaust gas composition, which was directly correlated with the speed of the corrosion process.…”
Section: Introductionmentioning
confidence: 99%
“…The research of Hardy et al [12] was focused on the high-temperature corrosion rates of steam boiler evaporators that use continuous measurements of flue gas composition and neural networks. Boilers in power stations are still the core of energy generation in many countries, and problems related to combustion, such as emissions [13], heat transfer, or corrosion [14], are still subjects of intensive investigation.…”
mentioning
confidence: 99%
“…Boilers in power stations are still the core of energy generation in many countries, and problems related to combustion, such as emissions [13], heat transfer, or corrosion [14], are still subjects of intensive investigation. Hardy et al [12] reported that measuring CO and O 2 concentrations near the water wall could be effectively supported by neural networks in evaporators' corrosion rate forecasting [12].…”
mentioning
confidence: 99%